Obstetric and neonatal outcomes of delayed interval delivery in cerclage: A retrospective study. (March 2020) - Nan, Yu; Wenyuan, Hu; Beejadhursing, Rajluxmee; Qingling, Kang; Wanjiang, Zeng; Dongrui, Deng; Suhua, Chen; Ling, Feng; Fuyuan, Qiao; Xun, Gong
Abstract: Objective: Delayed delivery is sometimes selectively performed in twin pregnancy when the first birth occurs inevitably in order to improve the prognosis and decrease the morbidity and mortality of the second twin. The aim of this study is to explore the maternal and fetal outcomes of pregnancies in which cerclage is carried out following the loss of first fetus in twin gestation for delayed interval delivery. Methods: Three cases of delayed-interval delivery of dichorionic-diamniotic twin pregnancies were reported in our center between 2017 and 2018 and were retrospectively analyzed. Once the first twin was delivered, the second twin was left in utero and the patient underwent in utero percutaneous umbilical cord ligation, antibiotics, tocolytic therapy and cervical cerclage. Results: Mean gestational age at delivery of the first fetuses was 21.6 ± 2.9 weeks and 24.8 ± 4.0 weeks for the remaining fetuses, respectively. The mean interval of the delay was 22 days (4–50 days). Mortality of the first fetus was 66.7%, and the retained one was 33.3%. In general, maternal outcome was good, one patient experienced postpartum hemorrhage and placenta accreta. However neonatal aftermath was generally not favorable, probably due to extreme prematurity. Conclusions: Cervical cerclage after the first delivery could prolong the pregnancy until an adequate gestational age at which an enhanced prognosis and better perinatal outcome for the second twin can be achieved.